An azidocoumarin-based fluorescent probe for imaging lysosomal hydrogen sulfide in living cells. Issue 19 (5th May 2017) - Xie, Qiao-Ling; Liu, Wei; Liu, Xian-Jun; Ouyang, Fan; Kuang, Yong-Qing; Jiang, Jian-Hui
Abstract : A commercially available fluorescent hydrogen sulfide (H2 S) probe 7-azido-4-methylcoumarin (AzMC) was developed into its lysosome-targeted counterpart Lyso-C via a four-step synthetic approach. Abstract : A commercially available fluorescent hydrogen sulfide (H2 S) probe 7-azido-4-methylcoumarin (AzMC) was developed into its lysosome-targeted counterpart Lyso-C via a four-step synthetic approach. Lyso-C displayed fast response (within 5 min), excellent sensitivity (with a detection limit of 37 nM) and high selectivity toward H2 S. More importantly, Lyso-C was successfully applied to imaging lysosomal H2 S and showed potential capability to quantitatively detect H2 S in living cells.